2022
DOI: 10.32604/cmes.2022.017304
|View full text |Cite
|
Sign up to set email alerts
|

Bioconvection Mangnetohydrodynamic Tangent Hyperbolic Nanofluid Flow with Quartic Chemical Reaction Past a Paraboloid Surface

Abstract: In this numerical study, the effect of quartic autocatalysis type of chemical reaction, buoyancy force and thermal radiation phenomenon and magnetic effect on tangent hyperbolic nanofluid past an upper horizontal surface of a paraboloid has been studied. By considering the Buongiorno model approach, a diffusion of unequal coefficients in the presence of gyrotactic microorganism is discussed. Implementation of microorganism's idea is used to stabilize the nanoparticles through bioconvection. The modeled PDEs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…ey showed that the velocity of the nanofluid is minimum near the wall, while an opposite trend is noted in the center of the channel. Atif et al [21][22][23] studied the radiative tangent hyperbolic nanofluid flow past a stretching sheet, a wedge, and a paraboloid surface of revolution. Khan et al [24] ascertained the double stratification effect on tangent hyperbolic nanofluid in a porous medium.…”
Section: Dynamics Of Multiple Slip Boundaries E Ect On Mhdmentioning
confidence: 99%
See 1 more Smart Citation
“…ey showed that the velocity of the nanofluid is minimum near the wall, while an opposite trend is noted in the center of the channel. Atif et al [21][22][23] studied the radiative tangent hyperbolic nanofluid flow past a stretching sheet, a wedge, and a paraboloid surface of revolution. Khan et al [24] ascertained the double stratification effect on tangent hyperbolic nanofluid in a porous medium.…”
Section: Dynamics Of Multiple Slip Boundaries E Ect On Mhdmentioning
confidence: 99%
“…Under the boundary layer approximation, the governing equations [16][17][18][19][20][21][22][23][24] are as follows:…”
Section: Mathematical Modelingmentioning
confidence: 99%